Microstructures and mechanical properties of wear-resistant titanium oxide coatings deposited on Ti-6Al-4V alloy using laser cladding. Issue 3 (March 2020) - Zhao, Yitian; Lu, Mingyuan; Fan, Zhiqi; McCormick, Paul; Tan, Qiyang; Mo, Ning; Huang, Han
Abstract: In this work, a freeze-dried TiO2 nano-sized powder was used as the coating material and single tracks of TiOx coating were cladded on Ti-6Al-4V substrates using a diode laser. The microstructure, chemical composition, and mechanical properties of the coatings were characterized and their relationships were explored. Coatings with structural and compositional gradients formed under a laser energy density (LED) of 20 kJ/m, while coatings with a relatively homogeneous microstructure were obtained using a LED of 30 kJ/m. The microstructure evolution was controlled by the molten pool lifetime and the intensity of convective flow during laser processing. The elastic modulus of the graded coating showed a decreasing trend from the top coating surface to the interface while that of the homogeneous coating remained constant. Our results also demonstrated that the hardness and wear resistance of the oxide coatings were up to four and ten times higher than that of the substrate.